Essays on Gurani Literature
XIII, 224 p. 49 illus., 6 illus. in color.
Keywords: This volume offers a new perspective on the Zagros region literary tradition. Gurani literature boasts a collection of the region’s oldest oral and written literary traditions. Despite its significance, the repertoire and its essential function in the preservation and transmission of historical, cultural, and literal data of the Guran region’s population has mostly remained unexplored. This volume represents various Guran regions on the southeastern and southern fringes of Kurdish territory and touches upon broad themes of oral and written texts, including epics, folktales, religious texts, poetry, and romances. These detailed and ground-breaking contributions will be an invaluable source for facilitating further research on the Gurani literary tradition; as well as being a significant guide to studying its impact on Persian and Zagros region literary history. Furthermore, this work will provide the reader with a new perspective and insight into the complexity and variety of literature in the Persianate world, moving toward a more inclusive view of literature.